Austria : Selected Issues. (IMF Staff Country Reports; Country Report, 2004)
This Selected Issues paper for Austria reports the impact of the government size, in addition to tax and expenditure composition, on real GDP growth. In addition to having a large public sector relative to the European Union (EU) 15 average, the composition of revenues is skewed, on the one hand, toward direct taxes. The distribution of expenditure, on the other hand, is broadly in line with the European Union (EU) 15 average. Austria is characterized by a heavy taxation of the factors of production, mainly labor, and to a lesser extent, capital.